EFEKTIVITAS PENGGUNAAN ASAM TRANEKSAMAT ORAL PADA PASIEN MELASMA - Al Mas - Nurissyita (Jurnal Ilmiah Kesehatan Media Husada, 2021)
This study aims to determine the effectiveness of using oral tranexamic acid in melasma patients, as well as to explain the definition of melasma, melasma epidemiology, melasma etiopathogenesis, and to explain the effectiveness of using oral tranexamic acid in melasma. The method used was to collect and analyze research articles on the effectiveness of the use of oral tranexamic acid topical drugs in Melasma patients. The articles are obtained through a search using Google Scholar, Pubmed. The term melasma comes from the Greek word "melas" which means black. Clinically melasma appears as macules or brown spots. Complaints of melasma usually occur symmetrically. The areas of melasma predilection are most commonly the cheeks, upper lip, chin and forehead, but can also be affected in other areas. (Debabrata, Handel et al., 2014). Research conducted for 6 months by Sufan et al ,. It is known that after therapy using Tranexamic Acid, there was a decrease in hyperpigmentation. After 6 months of treatment, the results were very good (10.8%, 8/74), good (54%, 40/74), moderate (31.1%, 23/74), and bad (4.1%). , 3/74). There were 4 patients (5.4%) who experienced mild gastrointestinal discomfort, 6 patients (8.1%) hypomenorrhea, subjects who rarely reported skin rash due to allergies as well as dizziness, alopecia, drowsiness and hyposexuality. From these results it is concluded that oral Tranexmatic Acid has good effectiveness in melasma therapy. (Sufan et al., 2012). From the results of this study it can be concluded that Tranexamic Acid has good effectiveness in the therapy of melasma. Where there are several risk factors that cause melasma, which can occur due to genetic factors, UV exposure, hormonal factors and inflammatory factors. Tranexamic acid will inhibit the action of tyrosinase activity by blocking the interaction of melanocytes and keratinocytes through inhibition of the plasminogen system. Keywords: Melasma, treatment for melasma, epidemiologi, etiologi, tranexamic acid,.